Myelin Debris Stimulates NG2/CSPG4 Expression in Bone Marrow-Derived Macrophages in the Injured Spinal Cord - Liu, Yang; Hammel, Grace; Shi, Minjun; Cheng, Zhijian; Zivkovic, Sandra; Wang, Xiaoqi; Xu, Pingyi; He, Xijing; Guo, Bing; Ren, Yi; Zuo, Li (Frontiers in Cellular Neuroscience, 2021)
Although the increased expression of members of the chondroitin sulphate proteoglycan family, such as NG2, have been well documented after injury to the spinal cord, a complete picture as to the cellular origins and function of this NG2 expression has yet to be made. Using a spinal cord injury mouse model, we describe how some infiltrated bone marrow-derived macrophages (BMDM) are early contributors to NG2 expression and secretion after spinal cord injury. We demonstrate for the first time that a lesion related form of cellular debris generated from damaged myelin sheaths has the ability to induce this increased NG2 expression in BMDM which then exhibit enhanced proliferation and decreased phagocytic capacity. These results suggest that BMDM may play a much more nuanced role in the spinal cord injury cascade than previously thought, including acting as early contributors to the NG2 component of the glial scar.